If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(x+2)+2x=7x-(3x-2)
We move all terms to the left:
4(x+2)+2x-(7x-(3x-2))=0
We add all the numbers together, and all the variables
2x+4(x+2)-(7x-(3x-2))=0
We multiply parentheses
2x+4x-(7x-(3x-2))+8=0
We calculate terms in parentheses: -(7x-(3x-2)), so:We add all the numbers together, and all the variables
7x-(3x-2)
We get rid of parentheses
7x-3x+2
We add all the numbers together, and all the variables
4x+2
Back to the equation:
-(4x+2)
6x-(4x+2)+8=0
We get rid of parentheses
6x-4x-2+8=0
We add all the numbers together, and all the variables
2x+6=0
We move all terms containing x to the left, all other terms to the right
2x=-6
x=-6/2
x=-3
| x+x=5-1+10 | | 3w+7+w=32 | | 3x-2x+7x=3+4-2 | | 5x+2x=6+4 | | 4x-6.2x=-8 | | 0.4(a+1.4)=0.72 | | −5(2x+3)=−3x+15−7x | | 2(3x+2)−1=4+3(2x+1) | | 91/3+x=25/6 | | 0.41*x=17 | | 12+2x=6x-4 | | 25/9–x=7/13 | | x+x-6=158 | | -2-6x=7x-41 | | 3x-5=-5x-29 | | 3+6x=1-x | | 12x+22=97-3x | | -5x+2=-6x+1 | | 10-2x=-10x-6 | | -3x=18,6 | | 3.2t=-8 | | 8^(x+4)=2^x | | -5x-9=7x-57 | | -7x+43=9x-13 | | C=25n+7 | | 5x+23=26 | | 2x-7=38+7x | | -30(3x-2)=70 | | -3x=15,3 | | 3(2x-1)=-57 | | 4f–12=36 | | 2. 4f–12=36 |